Pelaksanaan Manajemen Berbasis Sekolah (MBS) Pada SD Inpres Bira 1 Kota Makassar - nasaruddin nasaruddin; muslimin muslimin (Universitas Negeri Makassar, 2018)
Abstract. This research included descriptive survey research. The location of this study is the Inpres Bira 1 Elementary School of Makassar City with the consideration that in the early stages of the implementation of SBM it was possible to do well because of various supporting factors such as teacher resources (using more core teachers), facilities and infrastructure and school infrastructure which is sufficient. The results showed, first; The implementation of school-based management can be seen from the principal's performance on the various tasks and functions of school principals such as, the principal as manager, supervisor administrator, leader, innovator and motivator can run quite well. Second; that teacher performance is assessed through aspects such as completeness of teaching programs, presentation of subject matter, evaluation and analysis of student learning outcomes and improvement and enrichment programs, and third; the other elements are considered good enough and good cooperation with the school management, this is mostly due to the lack of academic ability of the community in the organization (school committee) so that they still have limitations to play an active role in activities such as the formulation of the mission, vision in planning and supervision school. Keywords: Management, school, and students. Abstract. This research included descriptive survey research. The location of this study is the Inpres Bira 1 Elementary School of Makassar City with the consideration that in the early stages of the implementation of SBM it was possible to do well because of various supporting factors such as teacher resources (using more core teachers), facilities and infrastructure and school infrastructure which is sufficient. The results showed, first; The implementation of school-based management can be seen from the principal's performance on the various tasks and functions of school principals such as, the principal as manager, supervisor administrator, leader, innovator and motivator can run quite well. Second; that teacher performance is assessed through aspects such as completeness of teaching programs, presentation of subject matter, evaluation and analysis of student learning outcomes and improvement and enrichment programs, and third; the other elements are considered good enough and good cooperation with the school management, this is mostly due to the lack of academic ability of the community in the organization (school committee) so that they still have limitations to play an active role in activities such as the formulation of the mission, vision in planning and supervision school.